2012
DOI: 10.1016/j.comnet.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient key management scheme for content access control for linear hierarchies

Abstract: The content access control problem appears in any context with a set of users and resources. The difference in access rights of the users defines classes where members of a given class have exactly the same access rights. A hierarchy can be defined on the classes. Linear hierarchies constitute a particulary interesting type of hierarchies. They appear in a wide range of applications such as secure multi-layered data streaming and communications within security corps. Many proposals have dealt with key manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…In 2011, De Santis et al [36] and in 2012, Hassen et al [37] proposed their schemes with better performance than the previous ones. The schemes [36] (TBEBF:time-bound encryption-based family and TBBEBF:time-bound broadcast encryption-based family) support dynamic updates in the hierarchy at the expense of an increase in the amount of public information.…”
Section: Related Workmentioning
confidence: 99%
“…In 2011, De Santis et al [36] and in 2012, Hassen et al [37] proposed their schemes with better performance than the previous ones. The schemes [36] (TBEBF:time-bound encryption-based family and TBBEBF:time-bound broadcast encryption-based family) support dynamic updates in the hierarchy at the expense of an increase in the amount of public information.…”
Section: Related Workmentioning
confidence: 99%
“…In 2011, De Santis et al [30], and in 2012, Hassen et al [31] proposed their schemes with better performance than the previous ones. The schemes in [30] (TBEBF:timebound encryption-based family and TBBEBF:time-bound broadcast encryption-based family) support dynamic updates in the hierarchy without the need of redistribution of private information but at the expense of an increase in the amount of public information.…”
Section: Related Workmentioning
confidence: 99%
“…The scheme's private key storage requirement is small as it needs only one key per class, but the amount of public storage need grows linearly with the number of classes and edges in the graph. On the other hand, the scheme in [31] has very competitive storage, bandwidth, and computation overheads in comparison with previous ones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we suggest that designers use other ways to represent the level‐based access relations. We would like to refer readers to Hassen's research paper , which uses linear model as shown in Figure . He proposed a hybrid scheme that is very simple, effective, and secure.…”
Section: Collusion Attackmentioning
confidence: 99%